The Hidden Face of Rubisco. (May 2018) - Pottier, Mathieu; Gilis, Dimitri; Boutry, Marc
Abstract : R ibu lose-1, 5-bis phosphate c arboxylase/o xygenase (Rubisco) fixes atmospheric CO2 into organic compounds and is composed of eight copies each of a large subunit (RbcL) and a small subunit (RbcS). Recent reports have revealed unusual RbcS, which are expressed in particular tissues and confer higher catalytic rate, lesser affinity for CO2, and a more acidic profile of the activity versus pH. The resulting Rubisco was proposed to be adapted to a high CO2 environment and recycle CO2 generated by the metabolism. These RbcS belong to a cluster named T (for trichome), phylogenetically distant from cluster M, which gathers well-characterized RbcS expressed in mesophyll or bundle-sheath tissues. Cluster T is largely represented in different plant phyla, including pteridophytes and bryophytes, indicating an ancient origin. Highlights: R ibu lose-1, 5-bis phosphate c arboxylase/o xygenase (Rubisco) is a highly abundant chloroplast enzyme that fixes atmospheric CO2 into organic compounds. It is composed of eight copies of a large subunit (RbcL) and eight copies of a small subunit (RbcS). Genes that encode a particular RbcS (named RbcS-T) have been recently discovered in several species from different plant phyla. They are phylogenetically distant from well-characterized genes encoding RbcS (named RbcS-M), which are typically expressed in mesophyll and bundle sheaths. Biochemical characterization of RbcS-T-containing Rubisco has revealed higher catalytic activity, higher Km for CO2, and an acidic shift of the activity versus pH profile.